Recurrent ovarian torsion in an adolescent after oophoropexy - Erin K. Fee; Rula V. Kanj; Holly R. Hoefgen (Elsevier, 2017)
Adnexal torsion is an uncommon but serious emergency in the pediatric population. Surgical management by detorsion of the affected structure has become the standard of care. However, management to prevent recurrence of torsion in the younger female population is still debated. This report describes a case of recurrent torsion and the considerations involved in its management. A healthy 14 year-old girl presented with a third occurrence of right ovarian torsion, previously treated with oophoropexy, and was found to have failure of oophoropexy with adhesions near the pelvic sidewall. Complications of oophoropexy are not well reported, but adhesions and damage to adjacent structures should be considered. Torsion recurrence after oophoropexy is an uncommon complication, and management options include immediate oophoropexy after detorsion, interval oophoropexy, or close post-operative monitoring.